2014
DOI: 10.1155/2014/616935
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training in Patients with Substance Use Disorder

Abstract: Patients with substance use disorder (SUD) suffer a higher risk of cardiovascular disease and other lifestyle diseases compared to the general population. High intensity training has been shown to effectively reduce this risk, and therefore we aimed to examine the feasibility and effect of such training in SUD patients in clinical treatment in the present study. 17 males and 7 females (32 ± 8 yr) in treatment were randomized to either a training group (TG), treadmill interval training in 4 × 4 minutes at 90–95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 50 publications
10
90
0
Order By: Relevance
“…Recent work has expanded this investigation to include withdrawal symptoms/craving for other drugs of abuse (9,1820), and feasibility for relapse prevention for other substance use disorders (2133). …”
Section: Overview Of Clinical Findingsmentioning
confidence: 99%
“…Recent work has expanded this investigation to include withdrawal symptoms/craving for other drugs of abuse (9,1820), and feasibility for relapse prevention for other substance use disorders (2133). …”
Section: Overview Of Clinical Findingsmentioning
confidence: 99%
“…The etiology of the health problems is certainly multifactorial, but there are indications that impairment of skeletal muscle and bone may be important contributors. Previously, we and others have shown that amphetamine users have impaired physical function and muscular strength [5,6], likely due to a lamentable lifestyle with little physical activity. Reduced muscle function is typically accompanied by attenuated bone health [7,8].…”
Section: Introductionmentioning
confidence: 84%
“…Previous research into HIIT for adults with mental illness has focused on patients with a particular diagnosis (e.g. schizophrenia, depression, substance use) [296][297][298][299] . Understanding the feasibility and acceptability of different exercise approaches for heterogeneous patient groups may guide the implementation of exercise programs in mental health services, where patient groups are likely to be diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence suggests that HIIT is a feasible exercise protocol for adults with mental illness. Mean attendance rates have ranged from 68%-92%, and attrition has ranged from 10%-36% 296,297,299,300 . Common reasons for withdrawal have been due to pain or physical discomfort from the exercise 296,300 , and lacking motivation 300 , however, no studies have compared the feasibility of HIIT and MICT.…”
Section: Objective 5: To Assess the Utility Of Two Different Kinds Ofmentioning
confidence: 99%
See 1 more Smart Citation